Pemenuhan Nafkah Dan Kepuasan Perkawinan Pada Keluarga Muslim Pedesaan Di Indonesia - Wijaya, Jufri Aldhi (LPPM UNHASY, 2025)
Academic debate regarding the relationship between financial support and marital satisfaction remains ongoing. Research in Western and East Asian countries tends to employ objective approaches to financial conditions, while the context of rural Muslim families in Indonesia—with the concept of nafkah (spousal maintenance) grounded in religious and socio-cultural values—has not been extensively studied empirically. This study aims to identify and analyze the determinant factors influencing marital satisfaction among rural Muslim families in Indonesia, with specific focus on the role of nafkah fulfillment, perceived adequacy, and its relevance to household harmony. This study employed a qualitative approach with data collection techniques including observation, in-depth interviews, and documentation (triangulation). The research was conducted in Bancong Village, Wonoasri District, Madiun Regency, East Java, Indonesia. The findings reveal that rural Muslim communities perceive the amount of nafkah as something that cannot be precisely determined, but rather depends on the husband's income and family needs. Household harmony is perceived as the comprehensive provision of affection and balance of spousal rights and obligations. More significantly, the community does not identify a direct relevance between the objective amount of nafkah and household harmony. The perception of nafkah adequacy—rather than absolute nominal value—emerges as a more essential factor in determining marital satisfaction. This research confirms that in the context of rural Indonesian Muslim families, subjective perception of financial support adequacy has a more significant influence on marital satisfaction compared to objective financial support amounts. These findings contribute to the development of contextual marital satisfaction theory and provide practical implications for marriage counselors and family social policymakers.